Studies on Antinociceptive, Antiinflammatory and Diuretic Activities of Methanol Extract of the Aerial Parts of Clerodendron viscosum Vent. - Khatry, Nirupama; Kundu, Juthika; Bachar, Sitesh Chandra; Uddin, Mohammad Nasir; Kundu, Joydeb Kumar (Dhaka University Journal of Pharmaceutical Sciences, 2007)
Dhaka Univ. J. Pharm. Sci. Vol.5(1-2) 2006 The full text is of this article is available at the Dhaka Univ. J. Pharm. Sci. website